Compras on-line nas redes sociais: uma análise explicativa pautada na teoria do comportamento planejado - Nascimento, Amanda Nunes do (2021)
This dissertation had as general objective to verify the role of internal and background factors of the Theory of Planned Behavior (TCP) in the intention of online purchase in social networks. For this purpose, four studies were carried out, in Study 1 a systematic review was carried out to integrate the main findings on the theme. From a total of 198 articles, 6 studies were selected, which demonstrated the scarcity of research on online purchasing from the TCP. In Study 2, a descriptive survey was carried out on the beliefs regarding online purchasing in social networks. Open questionnaires were applied with 30 participants from the city of João Pessoa - PB, aged between 19 and 37 years (M = 25.1 years, PD = 6.27; EP = 1.14). The data were transcribed and analyzed at IRAMUTEQ, where a Descending Hierarchical Analysis was conducted. In general lines, it was possible to evidence that beliefs are related to positive and negative aspects (affordable prices, delay in delivery) and were significantly affected by social influences (family, friends) and perceived conditions (ease, fear). In Study 3, the objective was to elaborate, test the factorial structure and verify the internal consistency of the online shopping scale in social networks. 250 volunteers participated in this study, mostly female (70.4%), aged between 18 and 61 years (M = 28.0 years; SD = 8.65; EP = 0,54). Through confirmatory analysis, the tetra-dimensional model presented the best adjustment rates. Thus, the factorial validity of the scale was corroborated with the TCP assumptions, and the final measurement consisted of 19 items. In addition, the internal consistency of the measurement can be verified, where alpha and omega of 0.93 were obtained. Finally, in Study 4, two explanatory models based on the PCT were tested. A total of 250 volunteers participated in this study, most of them female (67.2%) and aged between 18 and 71 years (M= 25.76; SD= 7.63; EP = 0,48). Through path analysis the models were tested and it was found that the original TCP model had better fit rates than the extended model. The effects of the constructs on the intention to purchase online on social networks 11 were also analyzed, where it was possible to observe that attitude and subjective norm were significant antecedents of the intention to purchase online on social networks and the perceived control was shown as an activator element of the norm in the intention. These results provide important subsidies about online buying behavior in social networks from a theoretical perspective consolidated in social psychology. Finally, it is hoped that the results presented and discussed in this dissertation can contribute to the academic community, specifically within the scope of social psychology and consumer behavior.